Authors versus literary critics Bolaño/Belano versus Echevarría/Echevarne - Rodrigues-Moura, Enrique (Revista de Filología Románica, 2017)
This essay ponders on the relationships between authors and literary critics in the contemporary literary field which is often in a state of conflict. It gives special consideration to the so-called “Echevarría case” (2004), in which the critic Ignacio Echevarría was confronted by the newspaper El País (Spain). This ultimately led to his resignation due to a clash of cultural, economical, as well as ideological interests. It closes with an analysis of Roberto Bolaños literary project and points out the poetological necessity of protecting it from literary criticism, especially considering that the novel Detectives salvajes (1998) is narrated through the characters Arturo Belano (author) and Iñaki Echevarne (literary critic).